2012
DOI: 10.1111/j.1440-1789.2012.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of O6‐methylguanine DNA methyltransferase (MGMT) and immunohistochemical analysis of 12 pineal parenchymal tumors

Abstract: Pineal parenchymal tumors (PPTs) are rare neoplasms which occupy less than 1% of primary central nervous system tumors. Because of their rare incidence, the previous reports on PPTs are limited in number and the useful molecular markers for deciding the histological grading and even selecting chemotherapy are undetermined. In this study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Although sensitive molecular markers of PPT have been identified in several small case series, the generalizability of these markers across PPT histologies is unclear. [35][36][37][38][39][40] Furthermore, it is unknown whether PPTs exist on a continuum; although there have been 2 reports of low-grade pineal neoplasms transforming to pineoblastomas and one case of pineocytoma disseminating to the leptomeninges, it remains to be established if these are indicative of true tumor biology. [41][42][43] The evolving understanding of pathological features and modifications in the classification scheme also accounts for some of the discrepancies in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although sensitive molecular markers of PPT have been identified in several small case series, the generalizability of these markers across PPT histologies is unclear. [35][36][37][38][39][40] Furthermore, it is unknown whether PPTs exist on a continuum; although there have been 2 reports of low-grade pineal neoplasms transforming to pineoblastomas and one case of pineocytoma disseminating to the leptomeninges, it remains to be established if these are indicative of true tumor biology. [41][42][43] The evolving understanding of pathological features and modifications in the classification scheme also accounts for some of the discrepancies in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, mitotic count and proliferative activity of papillary tumours of the pineal region have been detected as predictive factors for recurrence 27. MIB LI has been confirmed as a prognostic factor in a number of recent studies 3 18 19 27–29. Fèvre-Montange et al 26 reported that Ki67 LI may be helpful in distinguishing between grade II (mean 5.2) and grade III (mean 11.2) PPTID.…”
Section: Discussionmentioning
confidence: 96%
“…Also, grade II and grade III might present ++ NF staining and need to be further differentiated by mitotic count 5 7. Discrepancies of NF staining have been increasingly reported by recent histopathological studies and other PPTID specific markers have been proposed, such as MIB LI and Ki-67 LI, in the past decades 12 18 19 26. Most recently, mitotic count and proliferative activity of papillary tumours of the pineal region have been detected as predictive factors for recurrence 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 In a large cohort of patients with PPTID, Chalif et al found lack of survival advantage from chemotherapy 7 -these findings are consistent with a systematic review of 127 patients with PPTID 15 and reports of retained O 6 -methylguanine DNA methyltransferase promoter methylation status, which is likely to influence response to chemotherapy. 19 The authors determined that radiotherapy was independently associated with significantly increased survival; however, when radiotherapy was used as an adjuvant for surgically treated patients, it was only associated with significantly increased 5-year OS in patients with PPTID WHO grade 3. 7 These findings from Chalif et al 7 Resection group was associated with significantly higher PFS rates than the biopsy group (1-y 97% and 90% and 5-y 89% and 75%, respectively; P < .05).…”
mentioning
confidence: 99%